2014
DOI: 10.1186/1471-2261-14-63
|View full text |Cite
|
Sign up to set email alerts
|

Financial impact of adopting implantable loop recorder diagnostic for unexplained syncope compared with conventional diagnostic pathway in Portugal

Abstract: BackgroundTo estimate the short- and long-term financial impact of early referral for implantable loop recorder diagnostic (ILR) versus conventional diagnostic pathway (CDP) in the management of unexplained syncope (US) in the Portuguese National Health Service (PNHS).MethodsA Markov model was developed to estimate the expected number of hospital admissions due to US and its respective financial impact in patients implanted with ILR versus CDP. The average cost of a syncope episode admission was estimated base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…2,3 The advantages of this new ILR are its small size and streamlined delivery system, which allows for implantation outside of the cardiac catheterization laboratory. [4][5][6] The Reveal LINQt (Medtronic, Minneapolis, MN) also has an improved algorithm for the detection of both P waves and R waves, which correspond to the signals for atrial and ventricular depolarization, respectively, on the standard electrocardiogram. 7,8 This algorithm has been validated in adult patients to assist in P-wave detection.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 The advantages of this new ILR are its small size and streamlined delivery system, which allows for implantation outside of the cardiac catheterization laboratory. [4][5][6] The Reveal LINQt (Medtronic, Minneapolis, MN) also has an improved algorithm for the detection of both P waves and R waves, which correspond to the signals for atrial and ventricular depolarization, respectively, on the standard electrocardiogram. 7,8 This algorithm has been validated in adult patients to assist in P-wave detection.…”
Section: Introductionmentioning
confidence: 99%
“…Our work extends this finding, by comparing the ICM to PM insertion, and analyzes a subset of the patients with unexplained syncope included in the model by Providência et al. 32 …”
Section: Discussionmentioning
confidence: 63%
“…31 The ICM was not part of this model, and model inputs were heavily based on assumptions. 31 In another Markov model by Providência et al., 32 the ICM appeared to result in fewer syncope admissions and cost reductions for patients with unexplained syncope, compared with a conventional diagnostic pathway. Our work extends this finding, by comparing the ICM to PM insertion, and analyzes a subset of the patients with unexplained syncope included in the model by Providência et al.…”
Section: Discussionmentioning
confidence: 98%
“…It should be noted these studies were done in France and UK, respectively, where cost and reimbursement structures differ from those in the USA [30]. Other studies have found similar results [31]. Other studies looking at cost per quality-adjusted life (QALY) year have concluded SCRM implantation can be a cost-effective approach in infrequent syncope.…”
Section: Cost Effectivnessmentioning
confidence: 88%